Biotechnology policies for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The Intermediary Biotechnology Service (IBS) organized a regional meeting from 24 - 27 April 1995 in South Africa